2020
DOI: 10.1016/j.breast.2020.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Quality and reporting of clinical guidelines for breast cancer treatment: A systematic review

Abstract: Background High-quality, well-reported clinical practice guidelines (CPGs) and consensus statements (CSs) underpinned by systematic reviews are needed. We appraised the quality and reporting of CPGs and CSs for breast cancer (BC) treatment. Methods Following protocol registration (Prospero n o : CRD42020164801), CPGs and CSs on BC treatment were identified, without language restrictions, through a systematic search of bibliographic databases (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 60 publications
(117 reference statements)
1
26
0
Order By: Relevance
“…The standard was not comparable with the hypo fractionated radiation. The investigative subspecies investigation, hypo fractionation had all the earmarks of being less compelling for exceptional sarcoma comparing with poor-quality sarcoma [73]- [77]. The following experiments might be a successive result, yet this might rather mirror an alternate inalienable radiation affectability of superlative sarcoma or idiomatic subgroup of bosom malignant growth which were related to superlative sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…The standard was not comparable with the hypo fractionated radiation. The investigative subspecies investigation, hypo fractionation had all the earmarks of being less compelling for exceptional sarcoma comparing with poor-quality sarcoma [73]- [77]. The following experiments might be a successive result, yet this might rather mirror an alternate inalienable radiation affectability of superlative sarcoma or idiomatic subgroup of bosom malignant growth which were related to superlative sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…Each item was given a score from 1 (strongly disagree) to 7 (strongly agree). The overall quality scores ranged from 0% to 100%, and guidelines were classified as "high quality" if the AGREE II score was >80%, "moderate quality" if it was 50-80%, and "low quality" if <50% (14). Before the formal evaluation, all reviewers completed an online training tutorial to ensure standardization (10)(11)(12)(13).…”
Section: Quality Appraisal Of Guidelinesmentioning
confidence: 99%
“…The "reported" option was used when the relevant information was provided in the guideline, whereas "not reported" indicated that the relevant information could not be found or was unclear. The guidelines were classified as "well-reported" if the reporting rate was >80%, "moderate-reported" if it was 50-80%, and "low-reported" if <50% (14). Two rounds of pilot assessment of four guidelines were completed and the ICC value was calculated.…”
Section: Quality Appraisal Of Guidelinesmentioning
confidence: 99%
“…[10][11][12] Despite widely recognised principles and methods for developing sound CPGs, current research shows that guidelines on various topics lack appropriate uptake of systematic review methodologies in their development, 13 give recommendations that conflict with scientific evidence 14 or do not adequately take into account existing CPG quality and reporting assessment tools. 15 This emphasises the ongoing need to appraise guidelines to ensure evidence-informed care.…”
Section: Introductionmentioning
confidence: 99%